2016
DOI: 10.1177/0269758015627041
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the gap in perceptions of legitimacy of victims and non-victims

Abstract: Crime victims are a unique subgroup who evaluate the police and police legitimacy more harshly than those who have not been victimized. This could be explained by their victimization, and their special needs from and expectations of the police. Due to the importance of crime victims for the criminal justice system, the current study examines the mechanisms underlying differences in legitimacy evaluations of victims and non-victims. We focus on the two main antecedents of legitimacy: procedural justice and poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 101 publications
(180 reference statements)
0
7
0
Order By: Relevance
“…However, it is by no means guaranteed that law enforcement will be supportive when questioning CSEC victims. Crime victims often experience negative interactions with police officers (Aviv & Weisburd, 2016); reporting that officers questioned them in an insensitive, mistrustful, or dominant manner (Holmberg, 2004); and rape victims specifically report that law enforcement often questioned them with little displays of empathy (Logan et al, 2005; Maier, 2008; Patterson, 2011; Webster et al, 2020).…”
Section: Csec Victim Reluctancementioning
confidence: 99%
“…However, it is by no means guaranteed that law enforcement will be supportive when questioning CSEC victims. Crime victims often experience negative interactions with police officers (Aviv & Weisburd, 2016); reporting that officers questioned them in an insensitive, mistrustful, or dominant manner (Holmberg, 2004); and rape victims specifically report that law enforcement often questioned them with little displays of empathy (Logan et al, 2005; Maier, 2008; Patterson, 2011; Webster et al, 2020).…”
Section: Csec Victim Reluctancementioning
confidence: 99%
“…Researchers determined that police performance can have a lasting effect on whether citizens accept or reject police practices and the public's perception of the police (Aviv & Weisburd, 2016). Research that explored police performance perceptions showed that citizens perceived BWCs as beneficial to police performance (Crow et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature has consistently established that victims have more negative attitudes toward the police compared to non-victims, likely due to victims' positive/negative first-hand and vicarious experiences with police, or due to the trauma of victimization as well as possible secondary victimization when dealing with police (Aviv & Weisburd, 2016). Research into procedural justice and the willingness to report crime to police indicates that it is important to differentiate between crime types (Murphy & Barkworth, 2014).…”
Section: Risk Factors Of Victimization and Impact Of Victim Status Onmentioning
confidence: 99%
“…There has been increasing interest in the impact of victim status and crime type on perceptions of police legitimacy (see, e.g., Aviv & Weisburd, 2016;Murphy & Barkworth, 2014). Studies across varying geographical and policing contexts consistently suggest that people who have experienced a crime have more negative attitudes toward police compared with people who have no experience with victimization (Aviv & Weisburd, 2016); while other studies have found that the type of crime is another factor in need of consideration (Murphy & Barkworth, 2014). Positive public perceptions of the police and their legitimacy are important, as the police depend on the public's cooperation to solve crime.…”
Section: Introductionmentioning
confidence: 99%